Flexural Behavior of Self Compacting Concrete T-Beams Reinforced with AFRP - Sinan A.Yaseen (Zanco Journal of Pure and Applied Sciences, 2020)
In This paper, an experimental work is carried out to study behavior and performance of Self compacted concrete (SCC) T-section beams reinforced with Aramid fiber reinforced polymers (AFRP) bar. Key variables that taken into consideration were flexural reinforcement ratio, different self-compacted concrete mixes having different strengths. Normal strength steel bars for data comparison. 9 samples of T-sections were designed using (AFRP) to be weak in flexure. 3 samples of T-sections were used with normal steel bars as control samples for comparison. The effect of these fiber reinforcement contents on flexural behavior and crack pattern were observed during third-point loading tests. A data comparison was performed between experimental and analytical beam calculation using ACI 440 as an applied design source. The results show that the final deflection was more in AFRP compared with steel reinforced beams indicating to significant enhancement in strength and toughness. The ultimate capacity of AFRP beams increased more than steel reinforced beams by increasing self-compacting concrete strength. The reinforcement ratio improves the final resisting load as the ratio increases. The maximum observed crack-width in beams reinforced with AFRP bars is three to five times that of normal steel reinforced beams. The exactness of the data depends on both the compressive strength and reinforcement ratio for both AFRP and conventional steel bars. It is seen from data comparison between the experimental work and the ACI 440, That the ACI440 is more conservative when AFRP is used in SCC.